role of an occupational therapist in working with people with MS in the opinion of patients - Paulina Aleksander-Szymanowicz; Magdalena Paś; Katarzyna Filar-Mierzwa; Joanna Grapa; Aneta Bac (University of Applied Sciences in Tarnow, Poland, 2022)
Introduction: A person suffering from multiple sclerosis needs the care of numerous specialists, starting with the care of a doctor and a physiotherapist, and ending with an occupational therapist. Therefore, the purpose of the study was to assess the role of an occupational therapist in working with people with MS in the opinion of patients. Material and methods: 108 persons with multiple sclerosis aged 24 to 71 (average age 41.8 ±11.1) participated in the study. The research tool was the author's questionnaire consisting of 28 questions regarding the disease and the cooperation with an occupational therapist. The results were developed using descriptive statistics, which included the arithmetic mean, standard deviation, minimum value and maximum value. For statistical analysis, the R software was used, and all analyses were performed with the Chi-squared test and the Fisher's exact test with the Monte Carlo simulation method. Results and conclusions: During the exacerbation of the disease, the respondents had the greatest difficulty in getting dressed and getting out of bed or chair. The least problematic issue for the respondents was the continuation of their favourite activities, hobbies. Among the respondents, most of persons who regularly attended rehabilitation cooperated with an occupational therapist. Most of the respondents participated in occupational therapy held in a rehabilitation centre and indicated modifications of daily performed activities as a therapeutic intervention. In the group under study, most persons would like to cooperate with an occupational therapist individually at home. Among these persons, most would expect to develop alternative methods of performing important but difficult activities and to introduce auxiliary equipment during the exacerbation of the disease.